2014
DOI: 10.1128/aem.04162-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarker Genes To Predict Biodegradation of 1,4-Dioxane

Abstract: Bacterial multicomponent monooxygenase gene targets in Pseudonocardia dioxanivorans CB1190 were evaluated for their use as biomarkers to identify the potential for 1,4-dioxane biodegradation in pure cultures and environmental samples. Our studies using laboratory pure cultures and industrial activated sludge samples suggest that the presence of genes associated with dioxane monooxygenase, propane monooxygenase, alcohol dehydrogenase, and aldehyde dehydrogenase are promising indicators of 1,4-dioxane biotransfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 59 publications
1
54
0
Order By: Relevance
“…In comparison to the total bacteria counts, DXMO‐carrying microorganisms constituted up to 5.8 percent of the total bacterial community, which is significant as a previous study has shown that 1,4‐dioxane–degrading bacteria (carrying DXMO) as low as 2 percent of the total population were able to consume high levels of 1,4‐dioxane (Gedalanga et al., ). This site is unique to have >5 percent of the bacterial population with the DXMO gene.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In comparison to the total bacteria counts, DXMO‐carrying microorganisms constituted up to 5.8 percent of the total bacterial community, which is significant as a previous study has shown that 1,4‐dioxane–degrading bacteria (carrying DXMO) as low as 2 percent of the total population were able to consume high levels of 1,4‐dioxane (Gedalanga et al., ). This site is unique to have >5 percent of the bacterial population with the DXMO gene.…”
Section: Discussionmentioning
confidence: 90%
“…This may suggest both metabolic and cometabolic 1,4‐dioxane biodegradation pathways are active at this site. The presence of both DXMO and ALDH has been established as a strong indicator of 1,4‐dioxane biodegradation (Gedalanga et al., ). Remarkably, our 1,4‐dioxane biomarkers were highly associated with monitoring well locations with detectable levels for 1,4‐dioxane and THF, although THF concentrations were typically lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISB can be implemented by (1) allowing intrinsic microorganisms in the subsurface to biodegrade the COC without human intervention other than monitoring, referred to as natural attenuation; (2) supplying necessary amendments or nutrients to enhance biodegradation of the contaminant by the microorganisms, referred to as biostimulation; or (3) introducing microorganisms to the subsurface that have been shown to be capable of degrading the COC, referred to as bioaugmentation. In recent years, microcosm studies have been conducted to understand DX biodegradation rates under cold regimes (4 °C and 14 °C; Li et al., ), in the presence of co‐occurring metals and chlorinated solvents (Mahendra et al., ; Pornwongthong et al., ; Zhang et al., ), or under bioaugmentation conditions for direct metabolic biodegradation by CB1190 (Gedalanga et al., ; Kelley et al., ). All these microcosm studies built a better understanding of the feasibility of DX biodegradation for in situ or ex situ applications and optimum conditions needed for successful applications.…”
Section: In Situ Treatment Technologiesmentioning
confidence: 99%
“…Currently, genetic analysis based on 16S rRNA gene of specific bacteria and functional genes have been developed and applied in the field study (Behrens et al 2008;Da Silva and Alvarez 2008;Hendrickson et al 2002). These biomarkers became a practical molecular tool providing a rapid method for assessing the biodegradation of interest (Fennell et al 2001;Gedalanga et al 2014). To diagnose the chlorinated solvents degradation capability, Dehalococcoides 16S rRNA gene and dechlorination genes such as tceA, vcrA and bvcA (Krajmalnik-Brown et al 2004) have been successfully applied in the chloroethenes-contaminated groundwater in the US and Europe (Da Silva and Alvarez 2008;Lee et al 2008;Müller et al 2004;van der Zaan et al 2010).…”
Section: Introductionmentioning
confidence: 99%